Fintech and Financial Access: Demographic Drivers of Financial Inclusion in Indonesia - Sim, Yulia Melyanda; Dias Satria (Contemporary Studies in Economic, Finance and Banking, 2026)
This study explores the influence of infrastructural and demographic determinants on the adoption of FinTech in Indonesia using Global Findex 2021 data. The binary dependent variable is an indicator of mobile money or digital payments usage. Probit and Logit models are applied to examine such variables as employment, income, education, age, gender, rural residence, phone possession, and internet usage. Results show that education, employment, gender, mobile phone, and internet usage significantly and positively affect adoption, but income and age do not. Logit model fits better as per fit statistics and residual analysis. The results confirm the need for inclusive infrastructure and digital literacy to drive financial inclusion.